Ultrasound-assisted synthesis of MIL-88(Fe) coordinated to carboxymethyl cellulose fibers: A safe carrier for highly sustained release of tetracycline - Darvishi, Sima; Javanbakht, Siamak; Heydari, Abolfazl; Kazeminava, Fahimeh; Gholizadeh, Pourya; Mahdipour, Mahdi; Shaabani, Ahmad (International journal of biological macromolecules, 2021)
For stopping long-time harmful bacterial infection, designing a drug carrier with a highly prolonged release profile is a promising approach that is of interest to different biomedical areas. The subject of this work is to synthesis a novel carrier system through coordination of MIL-88(Fe) to carboxymethyl cellulose (CMC) for enhancing interaction between drug and carrier. We established an ultrasound-assisted synthetic method for in situ synthesis of MIL-88(Fe) in the presence of CMC resulting in CMC/MIL-88(Fe) composite. The CMC/MIL-88(Fe) was loaded with a high amount of Tetracycline (TC) by immersion of carrier to the TC aqueous solution. The release profile in the simulated physiological conditions, pH 7.4, revealed a low initial burst release followed by a sustained and prolonged release over 384 h. The in vitro cytotoxicity of CMC/MIL-88(Fe) against Human skin fibroblast (HFF-1) cells was calculated by MTT assay and showed a good cytocompatibility. The antibacterial activity was found for TC-loaded CMC/MIL-88(Fe) toward both E. coli and S. aureus with MIC 64 mg·ml−1.